Time-domain NMR relaxometery – a green analytical tool for estimating physico-mechanical properties of polyolefins. Issue 2 (17th February 2022) - Kapur, Gurpreet S.; Goel, Vishal; Luthra, Priyanka; Kumar, Ravindra; Tyagi, Hemant; Ramakumar, S. S. V.
Abstract: Physical and mechanical properties of PE and PP are traditionally determined in the laboratory with methods as specified in ASTM/ISO standards. This is a time-consuming activity in any QC laboratory. In this paper, low-field (20 MHz) NMR has been used to quickly determine properties like density of HDPE, Xylene Solubles (XS) in homo-polymer PP & impact copolymer polypropylene (ICP), ethylene content (C2), flexural modulus (FM) and Izod impact strength of ICP, within a short span of time (∼1/4 h), allowing the plant to get expeditious feedback about the manufactured polymer grade enabling monitoring the manufacturing process more efficiently. The novelty in this work is that even calibration and predictive models for determining mechanical properties of polyolefins like FM and Izod impact strength have been successfully developed. Calibration models were built using known samples and validated using the validated sample set. For HDPE samples, a calibration model for determining the density could be prepared with R 2 of 0.867 and RMSEC of 0.0006 gcm −3 . For homo PP samples, a predictive model for determining XS could be prepared with R 2 of 0.934 and RMSEC of 0.20 wt%. In case of calibration models for XS and C2 of ICP samples, R 2 = 0.924 each and RMSEC of 0.54 wt% & 0.45 wt%, respectively was obtained. A model for flexural modulus could be prepared with an R 2 and RMSEC of 0.935 & 28 MPa, respectively. Reasonable model could be developed for Izod impact strength ( R 2 = 0.947 & 0.982 for low & high impact respectively). The properties of validation sample set were predicted based on the calibration models and good correlation was obtained between the lab data (QC data) and the predicted data.